URGENSI KOMUNIKASI EFEKTIF BAGI VOLUNTEER PKBI KOTA SEMARANG MELALUI PELATIHAN PUBLIC SPEAKING - Liya Umaroh; Mutia Rahmi Pratiwi; Mukaromah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
PKBI Semarang city is a non-governmental organization which runs on reproductive health. Volunteer involvement during outreach activities can hone skills and self-confidence through public speaking experience. From the situation analysis, the problem was obtained such as lack of understanding and public speaking techniques. Therefore, it is important to schedule community service activities to provide effective communication training by implementing public speaking techniques. The method for implementing PKM activities uses training, facilities and mentoring methods through 6 stages, namely, preparation, intake process, assessment, planning, implementation and termination. To evaluate the results of the training activities, a pre-test and post-test were used which indicated that there was an increase in effective communication skills by providing public speaking training for PKBI volunteers. The sustainability of the activities is expected by the volunteers to support their activities because the volunteers' main activity is dealing with many people from different backgrounds, which requires them to be skilled in communicating effectively with skills in applying public speaking techniques